2010
DOI: 10.2522/ptj.20090150
|View full text |Cite
|
Sign up to set email alerts
|

A Balance Exercise Program Appears to Improve Function for Patients With Total Knee Arthroplasty: A Randomized Clinical Trial

Abstract: There is a need for conducting a larger randomized controlled trial to test the effectiveness of an FT+B program after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
135
0
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 56 publications
5
135
0
19
Order By: Relevance
“…Because being overweight or obese is a risk factor for poor postural stability (56)(57)(58), and because changes in body weight influence balance control (59,60), it is reasonable to expect that overweight and obese patients perform more poorly in the FRT and SLS test compared with patients with a normal BMI, because such tasks are highly dependent on postural stability and balance control. Previous studies have shown that the performance of postural stabilitydependent mobility tasks improves after balance-based post-TKR rehabilitation (24,38), which is consistent with the significant improvements in the FRT and SLS test results for all of the BMI groups at the 2-month and 6-month post-TKR followup assessments in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Because being overweight or obese is a risk factor for poor postural stability (56)(57)(58), and because changes in body weight influence balance control (59,60), it is reasonable to expect that overweight and obese patients perform more poorly in the FRT and SLS test compared with patients with a normal BMI, because such tasks are highly dependent on postural stability and balance control. Previous studies have shown that the performance of postural stabilitydependent mobility tasks improves after balance-based post-TKR rehabilitation (24,38), which is consistent with the significant improvements in the FRT and SLS test results for all of the BMI groups at the 2-month and 6-month post-TKR followup assessments in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also shown that exercise interventions can reduce physical disability in overweight or obese patients with knee OA (53-55), indicating that rehabilitation can reduce the limiting effects of high BMI on mobility in overweight or obese patients with OA. Studies of TKR have shown postoperative rehabilitation promotes the recovery of functional mobility in overweight and obese patients (38,49). In the current study, the outcome measures for all of the patients, including those with a high BMI, were improved by an active postoperative rehabilitation program.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Recent research has studied how exercise programs including functional training and balance can improve single leg stance. Piva et al examined whether a functional training program alone (FT group) or with a balance exercise program (FT + B group) could improve single leg stance performance in TKA patients at least 2 months out from surgery [46]. The FT group had mean preoperative SLS times of 11.7 ± 11.9 s and 11.0 ± 10.8 s on the surgical and non-surgical sides, respectively, while the FT + B group exhibited times of 16.4 ± 10.9 s and 11.0 ± 10.0 s on the surgical and non-surgical sides, respectively.…”
Section: Discussionmentioning
confidence: 99%